2022
DOI: 10.1371/journal.pone.0272424
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the progress on the implementation of policy and legislation actions to address the Non-Communicable Diseases crisis in the Pacific

Abstract: Aim To assess the progress on the implementation of Non-Communicable Diseases (NCD) related policies and legislations in the Pacific Island Countries and Territories (PICTs). Materials and methods The Pacific Monitoring Alliance for NCD Action (MANA) Dashboard was used to assess the progress on the implementation. The MANA Dashboard includes 31 indicators across four different domains such as leadership and governance; preventative policies and legislations; health system response programs; and monitoring Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This is currently monitored through the Pacific Monitoring Alliance for NCD Action (MANA) framework. According to the Pacific MANA, 15 PICTs have included physical activity as a compulsory component of the school curriculum 98 . School interventions that include promotion of daily physical activity also need to be strengthened in the region; like the Healthy Child Promising Future project implemented in Fiji and Wallis-and-Futuna, which assigns 30 minutes of daily physical activity to be included in school time 99 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is currently monitored through the Pacific Monitoring Alliance for NCD Action (MANA) framework. According to the Pacific MANA, 15 PICTs have included physical activity as a compulsory component of the school curriculum 98 . School interventions that include promotion of daily physical activity also need to be strengthened in the region; like the Healthy Child Promising Future project implemented in Fiji and Wallis-and-Futuna, which assigns 30 minutes of daily physical activity to be included in school time 99 .…”
Section: Discussionmentioning
confidence: 99%
“…As part of healthy lifestyles, this review found that sleep duration was linked to childhood OWOB. The association between sleep and weight status is well documented in the literature 98 , but there is limited anthropometric data available in the Pacific. WHO has released sleep time guidelines only for children under five years 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Food imports are influenced by price and availability fluctuations, as occurred during the global financial crisis in 2008 and more recently due to constraints related to the COVID-19 pandemic [ 3 ]. Trade agreements and efforts to support subsistence and commercial food production, for example through fishing [ 4 ], are in place across the Pacific but they are hampered by a lack of regional coordination and development assistance, and they seldom affect the livelihoods of the most vulnerable such as those living on outer Islands or in peri-urban areas [ 5 ]. This means that most Pacific countries are vulnerable to food security threats.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic changes present in chronic noncommunicable diseases have important components such as malnutrition due to excess, physical inactivity, and obesity, increasing the likelihood of developing cardiometabolic diseases. In addition, physical inactivity and a sedentary lifestyle are risk factors for the development of noncommunicable diseases and increased mortality (Mora et al, 2021;Win-Tin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%